Examining the human infectious reservoir for Plasmodium falciparum malaria in areas of differing transmission intensity - Bronner P. Gonçalves (Nature Portfolio, 2017)
Heterogeneity in the transmission potential of individual hosts is an important feature of malaria. Here, the authors perform a multi-regional study of the human infectious reservoir in malaria-endemic regions of Burkina Faso and Kenya.